Gyvenimo ir bibliografijos keliais ir klystkeliais - Vladimirovas, Levas (Knygotyra, 1980)
In the paper “True and mistaken pathes of life and bibliography” a characteristic is given of the activities of A. Ružancov, one of the eminent bibliographers of Lithuania of the bourgeois period. He was one of the founders of the Lithuanian library society and he organized the first statistical survey of libraries which has disclosed that the Lithuanian libraries were considerably lagging behind the most of European countries.Significant was also his contribution to the organization of bibliographic control of the Lithuanian book production and his systematic information in the press about the achievements of librarianship abroad.His life-long professional consistency stands in drastic contradiction to his political inconsistency which he disclosed for the first time during the civil war and several times afterwards.After the Soviet rule was re-established in Lithuania he tried to follow the new progressive course. he participated actively in introducing into the library practice the Soviet bibliographic classification and the new methods of work.But during the German occupation he again deserted to the bourgeois nationalist camp and in 1944 decided to leave his homeland. Living in West Germany he organized there a bibliographic service and began to publish a bibliographic index of the new Lithuanian bourgeois literature “The bookshelf”. But the lack of interest to this enterprise among the bourgeois emigrants made the publishing of this index a rather difficult affair.The last years of his life he lived in the USA, in the American atmosphere which was quite strange to him, and in very poor conditions of life. The ailing old man bad to work in a food store as ordinary worker. He died in 1966 far from his homeland and from all the great deeds which are being achieved here in various fields of the cultural life, bibliography, librarianship.